Audio Hiding Using Wavelet Transform with Amplitude Modulation - Ahmed, Waffaa S; George, Loay E (Al-Nahrain Journal of Science, 2018)
This research focus on using wavelet method for hiding secret data in the audio signal. The audio signal is transformed to frequency domain by using Haar wavelet transform. The wavelet coefficients are utilizied to host secret data with exact retrieval capability. For embedding process the magnitude modulation mechanism was applied. The introduced method makes checking for extracted hidden data to be sure that the host block can hold secret data, and can exactly reproduce the hidden data. The performance of hiding method was tested using the fidelity measures Mean Square Error (MSE), and Peak Signal to Noise Ratio (PSNR) to describe the overall error rate. Hiding rate was computed to asses the embedding power of this method. The test results indicated that the proposed system can give maximum hiding rate which is %5.10 when the value of threshold is 6, quantization step is 8 and block size is 16. The maximum PSNR is 42.94 when the block size value is 16, threshold value is 6, quantization step is 2, and don’t make subjective deterioration in quality of audio